Cocopeat Study with the Addition of NPK Fertilizer and Eco Enzyme as a Planting Medium for Water Spinach Microgreens - Aminullah, Aminullah; Indarwati, Indarwati; Haryanta, Dwi (Journal of Applied Plant Technology, 2025)
This study investigates the use of cocopeat as an eco-friendly planting medium, combined with NPK fertilizer and eco enzyme, to enhance the growth of microgreen water spinach. Cocopeat improves soil moisture and aeration, while NPK provides essential nutrients, and eco enzyme promotes microbial activity and root health. The experiment tested varying doses of NPK and eco enzyme in cocopeat, measuring plant height, leaf count, Vitamin A content, and sprout percentage. Results showed no interaction between NPK and eco enzyme treatments. The NPK solution in cocopeat (M2) yielded the highest growth values, while the control (M0) had the lowest. However, excessive NPK inhibited kale microgreen growth. Conversely, eco enzyme application alone did not significantly improve growth or quality. This research highlights cocopeat's potential as a sustainable medium but suggests careful NPK dosage to avoid growth suppression. While eco enzyme showed no direct impact, further studies could explore its role in nutrient absorption. The findings support eco-friendly cultivation techniques and offer insights into boosting Vitamin A in microgreen kale, contributing to sustainable agriculture and nutritional enhancement.